Verses in Motion: exploring sport in Polish and American poetry - Mazurkiewicz, Michał (Respectus Philologicus, 2025)
Sport has long been a subject of interest for writers from all over the world. As early as ancient Greek society, athletes who excelled in different sports disciplines were celebrated, a practice that also manifested in written form. This also concerns poets, inspired by the glories and shadows of sporting rivalry, noting its beauty and deep symbolism. The objective of this article was to examine (through historical examples and literary analysis) the phenomenon of sports poetry, a subject that has received scant attention from the research community thus far. The exploration focused on the literature of two countries – Poland and the United States, with a particular emphasis on the works of poets who perceive significant potential in sporting competition, such as – among others – Kazimierz Wierzyński, Krzysztof Zuchora, William Carlos Williams or William Heyen. The research methodology encompassed an examination of numerous volumes of poetry, perusal of publications (books and articles) dedicated to the presence of sport in literature, and an extensive review of the history of sport and literature. The findings show that sports poetry is still alive and remains an important – though academically neglected – segment of literature, embedding sport in the cultural sphere.